Corrigendum to “Hybrid vigor: Why hybrids with sustainable biofuels are better than pure electric vehicles” [Energy Sustain. Dev. Volume 76 (2023) 101261] (S0973082623001102), (10.1016/j.esd.2023.101261) - Gauto, Marcelo Antunes [UNESP]; Carazzolle, Marcelo Falsarella [UNESP]; Rodrigues, Marilene Elizabete Pavan [UNESP]; de Abreu, Ricardo Simões [UNESP]; Pereira, Tomaz Carraro [UNESP]; Pereira, Gonçalo Amarante Guimarães [UNESP] (Elsevier, 2024)
The authors regret to inform a small error in the bar's colours in Fig. 2. The numbers and concepts provided are correct and do not alter the content presented. Below is the adjusted figure with corrected colours. The authors would like to apologise for any inconvenience caused.